Cloud Manufacturing – An Approach to Strengthen Global Competitiveness of the Indonesian Small and Medium Manufacturing Enterprises (SMMEs) - Khamdi Mubarok, Mahrus Khoirul Umami (International Conference on Industrial Revolution for Polytechnic Education, 2019)
The World is moving into a new industrialrevolution era, Industry 4.0. Driven by the advanced developmentof computer science and information and communicationtechnologies (ICT), the German strategic initiative Industry 4.0has triggered many countries to establish their national strategiesto survive in current global industrial competition. Responding tothis trend, the Indonesian government recently launched “MakingIndonesia 4.0” as a roadmap to improve industrialcompetitiveness. Focusing on small and medium manufacturingenterprises (SMMEs), the Ministry of Industry also released ESmart IKM to help IKM (SMMEs) improve their productivity andexpand their market. However, these initiatives paid less attentionto the collaboration worth among companies. In order to build aclose relationship and strong collaboration among SMMEs, cloudmanufacturing concept is adopted in this research. By utilizing theInternet of things (IoT), service-oriented architecture (SOA)technologies and advanced cloud computing technologies, a cloudmanufacturing platform for the Indonesian SMMEs is developed.First, Making Indonesia 4.0 initiative and E-Smart program as thebackground of this research are observed. Second, cloudmanufacturing definition and basic concept are discussed.Finally, the adoption of cloud manufacturing and itsimplementation strategy for the Indonesian context are proposed.The initial work of this implementation is also presented.